2021
DOI: 10.1007/s12035-021-02339-4
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Ubiquitin Proteasome System in Glioma: Analysis Emphasizing the Main Molecular Players and Therapeutic Strategies Identified in Glioblastoma Multiforme

Abstract: Gliomas constitute the most frequent tumors of brain. High-grade gliomas are characterized by a poor prognosis caused by a set of attributes making treatment difficult, such as heterogeneity and cell infiltration. Additionally, there is a subgroup of glioma cells with properties similar to stem cells responsible for tumor recurrence after treatment. Since proteasomal degradation regulates multiple cellular processes, any mutation causing disturbances in the function or expression of its elements can lead to va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 217 publications
0
38
0
Order By: Relevance
“…Substrate proteins are stabilized and function under the combined regulation of the ubiquitin-proteasome system (UPS) and deubiquitinating enzymes (DUBs) [7]. The regulation of most key proteins determines cell proliferation, migration and apoptosis [8]. The pathways being regulated have different results depending on the ubiquitination site.…”
Section: Open Accessmentioning
confidence: 99%
“…Substrate proteins are stabilized and function under the combined regulation of the ubiquitin-proteasome system (UPS) and deubiquitinating enzymes (DUBs) [7]. The regulation of most key proteins determines cell proliferation, migration and apoptosis [8]. The pathways being regulated have different results depending on the ubiquitination site.…”
Section: Open Accessmentioning
confidence: 99%
“…The ubiquitinated proteins can be specially recognized by the 26S proteasome, and this leads to the proteasomal degradation of these proteins, regulating different cell processes. Many studies have revealed that the ubiquitin–proteasome system is involved in the progression of GBM 7 – 10 . A siRNA screening analysis showed that 22% of GBM-survival-relevant genes were components of the 20S and 26S proteasome subunits 11 .…”
Section: Introductionmentioning
confidence: 99%
“…NSC 144303 (G5) and NSC 632839 (F6), two DUBs inhibitors, are under pre-clinical trial 6 . Several DUBs were reported to regulate multiple cellular processes such as apoptosis, proliferation, and stemness in GBM 7 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the UPS is emerging as a promising source for the development of new therapeutic options for GB, and in particular PROTACs represent an interesting targeted therapy for the treatment of this devastating tumor ( Bufalieri et al, 2020b ; Scholz et al, 2020 ; Maksoud 2021 ; Farrell and Jarome 2021 ).…”
Section: Introductionmentioning
confidence: 99%